A Priori Bounds in Lp and in W2, p for Solutions of Elliptic Equations. (13th June 2013) - Monsurrò, Sara; Transirico, Maria
Abstract : We give an overview on some recent results concerning the study of the Dirichlet problem for second-order linear elliptic partial differential equations in divergence form and with discontinuous coefficients, in unbounded domains. The main theorem consists in an L p -a priori bound, P > 1 . Some applications of this bound in the framework of non-variational problems, in a weighted and a non-weighted case, are also given.